Bony Edema and Clinical Examination Findings Predict the Need for Distal Clavicle Excision at the Time of Shoulder Arthroscopy. Issue 1 (February 2022) - Garry, Conor B.; Adsit, Matthew H.; Land, Vaughn; Sanderson, Galen; Sheppard, Sean G.; Balazs, George C.
Background : Deciding to perform a distal clavicle excision for acromioclavicular joint arthritis, especially in conjunction with other arthroscopic shoulder procedures, is challenging for surgeons. Studies have reported mixed results on the value of magnetic resonance imaging (MRI) in decision making. Purpose : We sought to correlate MRI findings with clinical symptoms and the surgeon's decision to perform a distal clavicle excision. Methods : We compared MRI, clinical examination, and MRI findings of 200 patients who underwent distal clavicle excision for symptomatic acromioclavicular joint arthritis with 200 patients who underwent arthroscopic shoulder procedures for other reasons. Univariate statistics were used to determine correlations between physical examination findings, MRI findings, and the decision to perform distal clavicle excision. A binary logistic regression model was used to determine independent predictors of need for distal clavicle excision. Results : There was no difference in mean age, sex, and race between groups. Advanced acromioclavicular joint osteoarthritis was strongly correlated with positive physical examination findings. Bony edema correlated strongly with tenderness at the acromioclavicular joint but not pain with cross-body adduction testing. There was no association between higher MRI grade of osteoarthritis and the need for distal clavicle excision. Regression analysis identified both physical examination findings and bony edema on MRI as independent predictors of the need for distal clavicle excision. Conclusion : In the setting of positive clinical examination findings and bony edema of the distal clavicle, surgeons should feel reassured that distal clavicle excision is likely indicated.